Impact of Thoracic Endografting on the Hemodynamics of the Native Aorta: Pre- and Postoperative Assessments of Wall Shear Stress and Vorticity Using Computational Fluid Dynamics. (February 2021) - Midulla, Marco; Moreno, Ramiro; Negre-Salvayre, Anne; Beregi, Jean-Paul; Haulon, Stéphan; Loffroy, Romaric; Dake, Michael; Rousseau, Hervé
Purpose: To quantify the hemodynamic consequences of thoracic endovascular aortic repair (TEVAR) by comparing the preoperative and postoperative wall shear stress (WSS) and vorticity profiles on computational fluid dynamics (CFD) simulations. Materials and Methods: The pre- and postoperative computed tomography (CT) scans from 20 consecutive patients (median age 69 years, range 20–87) treated for different thoracic aortic pathologies (11 aneurysms, 5 false aneurysms, 3 penetrating ulcers, and 1 traumatic aortic rupture) were segmented to construct patient-specific CFD models using a meshless code. The simulations were run over the cardiac cycle, and the WSS and vorticity values measured at the proximal and distal landing zones were compared. Results: The CFD runs provided 4-dimensional simulations of blood flow in all patients. WSS and vorticity profiles at the proximal landing zone (located in zones 0–3 in 15 patients) varied in 18 and 20 of the cases, respectively; WSS was increased in 11 cases and the vorticity in 9. Pre- and postoperative WSS median values were 4.19 and 4.90 Pa, respectively. Vorticity median values were 40.38 and 39.17 Hz, respectively. Conclusion: TEVAR induces functional alterations in the native thoracic aorta, though the prognostic significance of these changes is still unknown. CFD appears to be a valuable tool to explore aortic hemodynamics, and its application in a larger series would help define a predictive role for these hemodynamic assessments.